Prescribing Patterns and Rationality of Antibiotic use in Toddler Patients at Raya Primary Health Center, Pematangsiantar City, Period January – March 2025 - Anggun Prety Adelia; Bulan Ramah Sagita; Agustina Agustina (Sean Institute, 2026)
The purpose of this study is to examine prescribing practices at the Raya Public Health Center in Pematangsiantar City and the extent to which antibiotics are used rationally in toddlers. The 126 antibiotic prescriptions reported during the study period were included in a descriptive quantitative study using a cross-sectional technique. This study shows that, according to WHO and Indonesian Ministry of Health criteria, the majority of antibiotic prescriptions (90.7%) are rational. Acute respiratory infections (ARI) and acute diarrhea are the most common illnesses requiring antibiotics. Rationality of antibiotic use and prescribing patterns are significantly correlated (p < 0.05) according to the Chi-Square test, although there is no significant correlation with age or gender.